Pengaruh Brand Image Terhadap Loyalitas Pasien Instalasi Rawat Jalan Rsud Haji Provinsi Sulawesi Selatan Tahun 2022 - Nurfitriani Nurfitriani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Service quality is a must and indicator to achieve patient satisfaction which ultimately facilitates the creation of patient loyalty. Excellent service increases patient satisfaction and ultimately patients remain loyal to the hospital. Patient loyalty is very necessary for the desire to use hospital service facilities in the long term, both for mutual interests, stakeholders and the hospital. Image is the name and characteristics of a product or service that is published through various media so that the brand can be remembered by consumers and can use the service for the second time. This study aims to analyze the influence of brand image on the loyalty of outpatient installation patients at the Hajj Hospital in South Sulawesi Province in 2022. The type of research conducted is quantitative research using observational studies with a cross sectional study design. The sample in this study were patients in the Outpatient Installation of the Haji Hospital, South Sulawesi Province, totaling 160 respondents. The results of the study show that there is a direct effect of brand image on patient loyalty in outpatient installations. It is suggested to hospital management to maintain and monitor evaluation by utilizing various media to carry out promotions in order to further expand and provide complete information about home service facilities, provide confidence. of hospital reliability, responsiveness in providing services to patients and understanding patient wishes.